Angiotensin‐Converting Enzyme 2 (SARS‐CoV‐2 receptor) expression in human skeletal muscle - Perez‐Valera, Mario; Martinez‐Canton, Miriam; Gallego‐Selles, Angel; Galván‐Alvarez, Victor; Gelabert‐Rebato, Miriam; Morales‐Alamo, David; Santana, Alfredo; Martin‐Rodriguez, Saul; Ponce‐Gonzalez, Jesus Gustavo; Larsen, Steen; Losa‐Reyna, Jose; Perez‐Suarez, Ismael; et al. (Scandinavian journal of medicine & science in sports, 2021)
The study aimed to determine the levels of skeletal muscle angiotensin‐converting enzyme 2 (ACE2, the SARS‐CoV‐2 receptor) protein expression in men and women and assess whether ACE2 expression in skeletal muscle is associated with cardiorespiratory fitness and adiposity. The level of ACE2 in vastus lateralis muscle biopsies collected in previous studies from 170 men (age: 19–65 years, weight: 56–137 kg, BMI: 23–44) and 69 women (age: 18–55 years, weight: 41–126 kg, BMI: 22–39) was analyzed in duplicate by western blot. VO2max was determined by ergospirometry and body composition by DXA. ACE2 protein expression was 1.8‐fold higher in women than men (p = 0.001, n = 239). This sex difference disappeared after accounting for the percentage of body fat (fat %), VO2max per kg of legs lean mass (VO2max‐LLM) and age (p = 0.47). Multiple regression analysis showed that the fat % (β = 0.47) is the main predictor of the variability in ACE2 protein expression in skeletal muscle, explaining 5.2% of the variance. VO2max‐LLM had also predictive value (β = 0.09). There was a significant fat % by VO2max‐LLM interaction, such that for subjects with low fat %, VO2max‐LLM was positively associated with ACE2 expression while as fat % increased the slope of the positive association between VO2max‐LLM and ACE2 was reduced. In conclusion, women express higher amounts of ACE2 in their skeletal muscles than men. This sexual dimorphism is mainly explained by sex differences in fat % and cardiorespiratory fitness. The percentage of body fat is the main predictor of the variability in ACE2 protein expression in human skeletal muscle.